2001
DOI: 10.1192/bjp.179.6.482
|View full text |Cite
|
Sign up to set email alerts
|

Cycle of child sexual abuse: Links between being a victim and becoming a perpetrator

Abstract: The data support the notion of a victim-to-victimiser cycle in a minority of male perpetrators but not among the female victims studied. Sexual abuse by a female in childhood may be a risk factor for a cycle of abuse in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(121 citation statements)
references
References 25 publications
3
103
1
14
Order By: Relevance
“…Dalsze zaniedbywanie doprowadziłoby do zaburzeń rozwoju psychospołecznego dziecka, prawdopodobnie skutkując uzależnieniem od środków odurzających [11]. Takie doświadczenia okresie dzieciństwa powodują także wzrost podatności dziecka na zaburzenia zdrowia fizycznego i psychicznego [12,13] i nasilają skłonności do przemocy w późniejszym życiu [14].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Dalsze zaniedbywanie doprowadziłoby do zaburzeń rozwoju psychospołecznego dziecka, prawdopodobnie skutkując uzależnieniem od środków odurzających [11]. Takie doświadczenia okresie dzieciństwa powodują także wzrost podatności dziecka na zaburzenia zdrowia fizycznego i psychicznego [12,13] i nasilają skłonności do przemocy w późniejszym życiu [14].…”
Section: Discussionunclassified
“…Continuation of this practice would have resulted in interference with the child's psychosocial development leading to lifelong psychological scars and possibly substance abuse [11]. Such experiences of a child can also increase the vulnerability of the child to mental and physical health problems [12,13] and result in them becoming perpetrators later in life [14].…”
Section: Discussionmentioning
confidence: 99%
“…Glasser et al (2001) found that the risk of perpetrating CSA was significantly enhanced by a history of CSA; for incest offenders, this risk was doubled. While, based on a sample of 182 child sex offenders, 57.7 per cent of the 79 intrafamilial offenders reported being a victim of CSA (Smallbone and Wortley, 2001).…”
Section: The Impact Of (If)csa (If)csa Has Psychological Behaviouralmentioning
confidence: 98%
“…Cinsel istismar›n ruhsal etkilerinin fliddetinde san›¤›n yafl›n›n ve cinsiyetinin etkisi yokken, ma¤durun yafl›n›n, cinsiyetinin, penetrasyon olup olmad›¤›n›n, istismar›n süresi ve bulundu¤u kültürün önemli etkisinin oldu¤u bildirilmifltir (3,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Ruhsal muayenesi yap›lan olgular›n %69,7'sinde eylemle iliflkilendirilebilecek ruhsal bir patoloji bulunmas› cinsel suçlar›n ruhsal aç›dan yaratt›¤› olumsuz etkileri göstermesi aç›s›ndan önemlidir.…”
Section: Tartifima Ve Sonuçunclassified